2017
DOI: 10.1371/journal.pone.0170960
|View full text |Cite
|
Sign up to set email alerts
|

Differential Feedback Regulation of Δ4-3-Oxosteroid 5β-Reductase Expression by Bile Acids

Abstract: Δ4-3-oxosteroid 5β-reductase is member D1 of the aldo-keto reductase family 1 (AKR1D1), which catalyzes 5β-reduction of molecules with a 3-oxo-4-ene structure. Bile acid intermediates and most of the steroid hormones carry the 3-oxo-4-ene structure. Therefore, AKR1D1 plays critical roles in both bile acid synthesis and steroid hormone metabolism. Currently our understanding on transcriptional regulation of AKR1D1 under physiological and pathological conditions is very limited. In this study, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…Anti-GAPDH antibodies (G9545) were obtained from Sigma-Aldrich (St. Louis, MO, USA). The specificity of those antibodies against the target proteins was demonstrated and reported previously (Valanejad et al, 2017; Song et al, 2014; He et al, 2011; Bellet et al, 2016). The specificity of AKR1D1 antibodies was evaluated with recombinant human AKR1D1 protein and the results were presented in Supplemental Fig.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…Anti-GAPDH antibodies (G9545) were obtained from Sigma-Aldrich (St. Louis, MO, USA). The specificity of those antibodies against the target proteins was demonstrated and reported previously (Valanejad et al, 2017; Song et al, 2014; He et al, 2011; Bellet et al, 2016). The specificity of AKR1D1 antibodies was evaluated with recombinant human AKR1D1 protein and the results were presented in Supplemental Fig.…”
Section: Methodssupporting
confidence: 65%
“…As a key player in bile acid synthesis and steroid hormone metabolism, our current understanding on AKR1D1’s roles in metabolic disease and diabetes is limited (Valanejad et al, 2017). In this study, we found that AKR1D1 expression was markedly repressed in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the degree of involvement of BAs in organs, excluding the liver, G protein-coupled receptor (TGR5) was reported as membrane-type BA receptor that is activated by BAs in the order of LCA > DCA > CDCA > CA in intestinal neuroendocrine cells, as well as the gall bladder, spleen, brown adipose tissue, macrophages, and cholangiocytes [ 40 , 41 ]. Therefore, BAs are pivotal signaling molecules stimulating FXR or TGR5 in many organs [ 15 , 42 , 43 , 44 , 45 , 46 , 47 ]. Additionally, HSCs activated in response to liver injury express TLR4, which promotes the activation of IκB kinase/NF-κB and JNK pathways in addition to the secretion of IL-6, transforming growth factor-β (TGF-β1), and monocyte chemoattractant protein 1 (MCP-1) [ 48 ]; however, it is unclear how these processes can be inhibited, which requires future studies.…”
Section: Discussionmentioning
confidence: 99%
“…GCs are known to increase 11β-HSD1 activity and expression and this has been postulated as a mechanism driving local GC excess and fueling an adverse metabolic phenotype (Jamieson et al 1995, Dube et al 2015. While the differential feedback of BAs to regulate AKR1D1 expression has been previously described (Valanejad et al 2017), to date, the interplay between GCs and AKR1D1 expression and activity has not been explored.…”
Section: Introductionmentioning
confidence: 99%